Imaging in gynecological disease (17): ultrasound features of malignant ovarian yolk sac tumors (endodermal sinus tumors). (1st August 2020) - Anfelter, P.; Testa, A.; Chiappa, V.; Froyman, W.; Fruscio, R.; Guerriero, S.; Alcazar, J. L.; Mascillini, F.; Pascual, M. A.; Sibal, M.; Savelli, L.; Zannoni, G. F.; et al.
ABSTRACT: Objective: To describe the clinical and sonographic characteristics of malignant ovarian yolk sac tumors (YSTs). Methods: In this retrospective multicenter study, we included 21 patients with a histological diagnosis of ovarian YST and available transvaginal ultrasound images and/or videoclips and/or a detailed ultrasound report. Ten patients identified from the International Ovarian Tumor Analysis (IOTA) studies had undergone a standardized preoperative ultrasound examination, by an experienced ultrasound examiner, between 1999 and 2016. A further 11 patients were identified through medical files, for whom ultrasound images were retrieved from local image workstations and picture archiving and communication systems. All tumors were described using IOTA terminology. The collected ultrasound images and videoclips were used by two observers for additional characterization of the tumors. Results: All cases were pure YSTs, except for one that was a mixed tumor (80% YST and 20% embryonal carcinoma). Median age at diagnosis was 25 (interquartile range (IQR), 19.5–30.5) years. Seventy‐six percent (16/21) of women had an International Federation of Gynecology and Obstetrics (FIGO) Stage I–II tumor at diagnosis. Fifty‐eight percent (11/19) of women felt pain during the ultrasound examination and one presented with ovarian torsion. Median serum α‐fetoprotein (S‐AFP) level was 4755 (IQR, 1071–25 303) µg/L and median serum CA 125 level was 126 (IQR, 35–227) kU/L. On ultrasound assessment, 95% (20/21) of tumors were unilateral. The median maximum tumor diameter was 157 (IQR, 107–181) mm and the largest solid component was 110 (IQR, 66–159) mm. Tumors were classified as either multilocular‐solid (10/21; 48%) or solid (11/21; 52%). Papillary projections were found in 10% (2/21) of cases. Most (20/21; 95%) tumors were well vascularized (color score, 3–4) and none had acoustic shadowing. Malignancy was suspected in all cases, except in the patient with ovarian torsion, who presented a tumor with a color score of 1, which was classified as probably benign. Image and videoclip quality was considered as adequate in 18/21 cases. On review of the images and videoclips, we found that all tumors contained both solid components and cystic spaces, and that 89% (16/18) had irregular, still fine‐textured and slightly hyperechoic solid tissue, giving them a characteristic appearance. Conclusion: Malignant ovarian YSTs are often detected at an early stage, in young women usually in the second or third decade of life, presenting with pain and markedly elevated S‐AFP. On ultrasound, malignant ovarian YSTs are mostly unilateral, large and multilocular‐solid or solid, with fine‐textured slightly hyperechoic solid tissue and rich vascularization. © 2020 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of the International Society of Ultrasound in Obstetrics and Gynecology..